2022
DOI: 10.1176/appi.neuropsych.21070181
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Neuroimaging Findings in Catatonia: Neuroradiological Reports of MRI Scans of Psychiatric Inpatients With and Without Catatonia

Abstract: ObjectiveCatatonia is a debilitating psychomotor disorder. Previous neuroimaging studies have used small samples with inconsistent results. We aimed to describe the structural neuroradiological abnormalities in clinical MRI brain scans of patients with catatonia and compare them to psychiatric inpatients without catatonia. We report the largest study of catatonia neuroimaging to date. MethodsIn this retrospective case-control study, neuroradiological reports of psychiatric inpatients who had undergone MRI brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We have previously identified a large cohort of 1,456 patients with catatonia from the CRIS database and have described their demographics, clinical characteristics, recreational drug use, laboratory test results and structural neuroimaging findings ( 24 26 ). In brief, this cohort was selected by sequentially conducting a search in the free text of the notes for the string “cataton*,” using a natural language processing app to remove clearly irrelevant entries followed by investigators manually screening notes.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously identified a large cohort of 1,456 patients with catatonia from the CRIS database and have described their demographics, clinical characteristics, recreational drug use, laboratory test results and structural neuroimaging findings ( 24 26 ). In brief, this cohort was selected by sequentially conducting a search in the free text of the notes for the string “cataton*,” using a natural language processing app to remove clearly irrelevant entries followed by investigators manually screening notes.…”
Section: Methodsmentioning
confidence: 99%
“…In the largest study of catatonia neuroimaging on psychiatric inpatients to date, it was found that magnetic resonance imaging (MRI) scan abnormalities were common in patients with catatonia, and mostly consisted of diffuse cerebral atrophy rather than focal lesions. However, the rates of those abnormalities did not differ between patients with catatonia and other psychiatric inpatients [17]; thus, structural neuroimaging findings cannot be used as biomarkers in catatonia. On the other hand, studies with the use of functional MRI neuroimaging have found a cerebral blood flow increase in the left supplementary motor area and lateral premotor cortex in acute and remitted patients with periodic catatonia, suggesting that these findings could be used as diagnostic biomarkers [18].…”
Section: Introductionmentioning
confidence: 90%
“…A systematic review of structural and functional brain imaging in catatonia, which identified 137 case reports and 18 studies with multiple patients (pooled n = 186), found that more than 75% of cases of catatonia were associated with non-focal brain imaging abnormalities affecting several brain regions, and associated with a variety of underlying conditions, including neuroinflammatory conditions (SLE, encephalitis) ( Haroche et al, 2020 ). The most common abnormalities in catatonia are generalised atrophy and non-specific white matter abnormalities ( Haroche et al, 2020 ; Jeyaventhan et al, 2022 ; Magnat et al, 2022 ).…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…In terms of focal neurological lesions in catatonia, there are case reports of catatonia associated with lesions to the frontal, parietal and temporal lobes, basal ganglia, diencephalon and cerebellum and lesions around the third ventricle. However, larger studies have found that most of the structural neuroimaging abnormalities in catatonia consist of generalised atrophy or non-specific white matter abnormalities ( Jeyaventhan et al, 2022 ; Magnat et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%